Implementation of the Public Blockchain Technology System in the Future to Increase Tourist Visits in Tangerang City - Aropria Saulina; Ariana Delhi (Blockchain Frontier Technology, 2024)
This research discusses the implementation of a public blockchain technology system in the future to enhance tourist visits to the city of Tangerang. The research method used is qualitative with a content analysis approach, involving the participation of relevant stakeholders, including the Tourism Office, travel agencies, destination managers, and tourists. The research findings indicate that the use of a public blockchain system, focusing on the concepts of decentralization, security, and cost reduction, has the potential to significantly increase tourist visits to the city of Tangerang. This method enables the involvement of the entire tourism ecosystem, strengthening trust and transparency, and providing innovative solutions to enhance the tourist experience. The conclusion of this research emphasizes that the implementation of blockchain technology in the tourism sector can be a key driver of industry growth and create a sustainable ecosystem. It is expected that these findings contribute to stakeholders in planning and implementing innovative solutions to enhance the attractiveness of Tangerang City as a tourist destination.